NILAI -NILAI PENDIDIKAN DALAM LAGU ANAK BALAM PADA PERTUNJUKAN RABAB PASISIE DALAM PESTA PERKAWINAN NAGARI KAMBANG KABUPATEN PESISIR SELATAN - Randi Suriandi; Tulus Handra Kadir; Syeilendra Syeilendra (SENDRATASIK UNP, 2012)
This article aims to describe the values ​​of education contained in the presentation of the song in the show Kids Balam Rabab Pasisie art. The study was conducted with a qualitative approach with descriptive methods. Object of study is the son Balam song presented in the show Rabab Pasisie. Research instrument is the researcher himself as a key instrument and data collection techniques using observation, interviews, documentation and literature. Data analysis was performed with an ethnographic approach. This study found that children Balam song in the show Rabab Pasisie, currently in demand by the public Kambang nagari, because both humanitarian messages regarding the relationship between mother and child, the universe and man's relationship with man. Through the presentation of the song Child Balam, the values ​​can be interpreted to be educational for the community pembelajran Kambang, such as the values ​​of brotherhood, the values ​​of love between mother and child, the values ​​of the forces of nature, both the power of the supernatural and the real force of nature. Through the presentation of the song Child Balam, Kambang nagari society, can be guided by these values ​​either through actions or attitudes and behavior in everyday life. Keywords: values ​​education, lagu anak balam, Rabab Pasisie